Estudio del comportamiento de los residuos provenientes del sector de la construcción privada y pública de la ciudad de Santiago de Cali, a partir de la obtención de agregado grueso y fino para el concreto - Vargas Piedrahita, Alejandra (Universidad de San Buenaventura - Cali, 2016)
The research was aimed to evaluate the effect on the physical and mechanical behavior of the incorporation of recycled aggregate in concrete, to fulfill the purpose of the investigation gravel, sand and debris were used. To accomplish this project was first conducted sampling, then manually separated to go to the crushing operation, having the particles having a particle size analysis based on the NTC-77 standard is performed, the test with a brand PINZUAR electric Sieving was performed, to identify the variability of aggregate grading density tests were performed, this test was conducted under the NTC-176 standard; finally concrete mixes recycled aggregates from the ACI method is performed, the mechanical behavior by NTC-673 standard was assessed, the cylinders were evaluated by the Universal Testing Machine PINZUAR PC42D references. (1) Identified as relevant data that 87.3% of the amount of debris is constituted by waste reusability as coarse aggregate, because they are constituted by brick, concrete and stone. Only 12.7% of the debris is composed of unwanted material to the valuation process of debris; which consists of organic matter, lime, metal, plaster and glass. It was established that the No3 mixture which was formed by adding 45% traditional and 55% aggregate recovered, showed the best mechanical behavior resisting 24.7 MPa, a density of 2.1 kg / m3 and 3% water absorption.